Storm echo - Singh, Nalini, 1977- (Singh, Nalini, 1977- Psy-changeling trinity novel., 2022)
"TARGET CONSUMER: For readers of paranormal romance, and fans of Christine Feehan and J. R. Ward. The next novel in the mesmerizing Psy-Changeling Trinity series by New York Times bestselling author Nalini Singh. In terms of age, Ivan fell in the older cadre of Ena's grandchildren. Younger than Canto, older than Silver and Arwen. He'd also always been the one who gave the family the least trouble-no trouble at all really. Canto was as stubborn as a bull and Silver had a steely spine, and neither ever bent for Ena unless they wished to do so. As for Arwen, gentle, empathic Arwen could be obstinate in his own way. Like water running over stone. Slow and relentless until the edges of the rock were no longer so sharp, and the water had carved a new channel without the rock ever being aware of the change. Ivan, in contrast, was more wont to say yes than no. Ask any of the other three and they'd never use the words obstinate or stubborn in relation to Ivan. One of the teenage members of the family had used the term "chill" to describe Ivan, and when Ena had looked up what that term meant when used in that context, she'd had to agree"--